1991
DOI: 10.1073/pnas.88.12.5428
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor expression is regulated by corticotropin in the human fetal adrenal: a model for adrenal growth regulation.

Abstract: Human fetal adrenal growth after midgestation is very rapid and appears to be dependent upon pituitary adrenocorticotropin (ACTH) in vivo. We hypothesized that the regulation of fetal adrenal growth by ACTH is mediated by ACTH-stimulated local growth factor production. As we have found basic fibroblast growth factor (bFGF) to be a potent mitogen for human fetal adrenal cells in culture, we conducted studies to determine whether bFGF is synthesized by the human fetal adrenal gland and whether bFGF gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…In adrenal cortex, FGF2 has long been considered a candidate for participating in the control of adrenal gland development in the fetus and also of growth and function in the adult adrenal cortex tissue (17). In this article we present an overview of our recent work focusing on the interaction between ACTH and FGF2 in cell cycle control of the Y1 adrenocortical tumor cell line.…”
Section: Introductionmentioning
confidence: 99%
“…In adrenal cortex, FGF2 has long been considered a candidate for participating in the control of adrenal gland development in the fetus and also of growth and function in the adult adrenal cortex tissue (17). In this article we present an overview of our recent work focusing on the interaction between ACTH and FGF2 in cell cycle control of the Y1 adrenocortical tumor cell line.…”
Section: Introductionmentioning
confidence: 99%
“…It is a basic rule that the mutations that give rise to cancer development are deletions of tumor suppressor genes or amplifications of oncogenes. The increase in cell proliferation induced by growth factors like the IGFs, bFGF or TGF 1 (Feige et al, 1991;Mesiano et al, 1991;Mesiano et al, 1993) leads to the development of polyclonal tumors but also renders the cells more susceptible to mutations in tumor suppressor genes or in oncogenes and if these mutations give those cells a genetic advantage, cancer development may ensue. Genomic instability is the basis of gross chromosomal alterations and aneuploidy (Giordano et al, 2009).…”
Section: Adrenal Cortex Cancermentioning
confidence: 99%
“…Although in vitro studies have shown that ACTH has the capacity to stimulate the expression of IGF-II (Voutilainen & Miller 1987, Ilvesmaki et al 1993b, Mesiano et al 1993 and bFGF (Mesiano et al 1991) by human fetal adrenal cells in culture, only a few in vivo studies have been conducted on this aspect of development in the primate. For example, Ducsay et al (1991) showed that ACTH regulated morphologic maturation of the baboon fetal adrenal gland, while Coulter et al (1996) demonstrated that adrenal growth and IGF-II expression were enhanced in fetal rhesus monkeys in which endogenous ACTH release was increased by the administration of metyrapone.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fetal adrenal expresses the messenger ribonucleic acids (mRNAs) and proteins for insulin-like growth factor-II (IGF-II) (Han et al 1987, 1992, Voutilainen & Miller 1988 as well as its respective binding proteins and receptors (Ilvesmaki et al 1993a, Coulter et al 1996, and basic fibroblast growth factor (bFGF) (Mesiano et al 1991). Moreover, in vitro studies have shown that IGF-II and bFGF stimulate fetal adrenal growth and their production may depend on ACTH , Simonian & Gill 1981, DiBlasio et al 1990, Mesiano et al 1993.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation